The legacy of the terrible mother archetype in postwar British drama: Ann Jellicoe's The Sport of My Mad Mother - Gülter, Işil Şahin (IGI Global, 2020)
The theatre provides the playwrights with a public platform through which they open up a more comprehensive framework to reinterpret the concept of the feminine. The chapter, in which translation remains a fundamental instrument that will be utilized to offer new interpretations to old ideas about the feminine, explores how the post-war British woman playwright Ann Jellicoe translates a women-related myth and reinterprets the concept of the feminine in The Sport of My Mad Mother (w.1958, r.1962). In this context, the chapter focuses on the concept of the Terrible Mother archetype which represents the female creative power as well as the potential for destruction in the play within a special reference to Jung's premises on the archetypal nature of the femininity and maternity. Thus, the chapter indicates that Ann Jellicoe, taking on board and challenging the perceived social, ideological, and psychological ideals of femininity, reclaims the legacy of the female strength. © 2021, IGI Global.